2021
DOI: 10.6007/ijarbss/v11-i11/11661
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Empowering Farmers through Technology Adoption towards Poverty Alleviation in Developing Countries

Abstract: Poverty alleviation is critical to improving the living standards of communities that earn less than $1 per day; the majority of them work in agriculture in developing countries. Lack of technological adoption is a significant factor influencing agricultural performance and minimizes the income of the poor rural community in many developing countries. The primary goal of this paper is to empirically validate the link between empowerment and technology adoption in the context of poverty alleviation. The current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Empowerment strategies are an integral part of poverty reduction efforts, as they involve increasing the capacity of individuals and communities to improve their socioeconomic conditions (Herath et al, 2021). Interestingly, while some studies report positive results from empowerment-focused programs, such as the National Program for Community Empowerment (PNPM), in urban areas (Cai et al, 2024), others suggest that such programs have not significantly reduced poverty rates in certain areas, such as the Sleman district (Yao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empowerment strategies are an integral part of poverty reduction efforts, as they involve increasing the capacity of individuals and communities to improve their socioeconomic conditions (Herath et al, 2021). Interestingly, while some studies report positive results from empowerment-focused programs, such as the National Program for Community Empowerment (PNPM), in urban areas (Cai et al, 2024), others suggest that such programs have not significantly reduced poverty rates in certain areas, such as the Sleman district (Yao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…While findings suggest empowerment can lead to positive outcomes, its effectiveness can vary based on implementation, local context, and other factors. Studies collectively underscore the importance of empowerment in poverty alleviation, whether through community self-organization, technology adoption, or collaborative governance (Herath et al, 2021;Khasanah et al, 2021). However, mixed outcomes require a deeper understanding of the conditions under which empowerment strategies can be most effective in reducing extreme poverty.…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of living standard on the decision to adopt indicated that as the living standard of households increases, the probability to adopt ILV would decrease, which is contrary to the a priori expectation. Standard of living is often modelled as a function of technology adoption (Chatterjee & Kar, 2017;Herath et al, 2021). The implication is that in this study, the effect of living standard on adoption of ILV would be biased.…”
Section: Determinants Of Adoption Of Improved Legume Varietiesmentioning
confidence: 95%
“…Therefore, farmers can have a better cognition of its benefits and risks as well as the cost, and they will also know the specific usage methods and maintenance points of technologies, etc. Hence, organizational empowerment can help farmers adopt and apply SWC [30].…”
Section: Robustness Analysismentioning
confidence: 99%